2021
DOI: 10.1002/aisy.202100001
|View full text |Cite
|
Sign up to set email alerts
|

Gas‐Lubricated Vibration‐Based Adhesion for Robotics

Abstract: Controllable adhesion, the ability to selectively attach or detach from a surface, is an essential capability for many engineered systems, such as material processing equipment, wall-climbing robots, and pick-and-place machinery. Robots capable of controllable adhesion have applications for inspection and repair, surveillance, and exploration of environments unsuitable for humans. [1,2] A variety of controllable adhesion techniques have been proposed to enable these use cases, including methods relying on pneu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…Therefore, it seems most appropriate to interpret the variation with of the levitation forces and moment as a variation with the levitation height . The latter is typically a ‘dependent’ variable that responds freely to changes in the load , for instance, the change in apparent weight of a mobile robot as it travels along a curved path as in figure 2( b ) (Weston-Dawkes et al., 2021). (Note that, for oscillators with sufficiently low mass or flexural rigidity, and may be affected significantly by variations in and the tilt angle (Ilssar & Bucher, 2017; Weston-Dawkes et al., 2021); such coupled interactions are not considered below.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, it seems most appropriate to interpret the variation with of the levitation forces and moment as a variation with the levitation height . The latter is typically a ‘dependent’ variable that responds freely to changes in the load , for instance, the change in apparent weight of a mobile robot as it travels along a curved path as in figure 2( b ) (Weston-Dawkes et al., 2021). (Note that, for oscillators with sufficiently low mass or flexural rigidity, and may be affected significantly by variations in and the tilt angle (Ilssar & Bucher, 2017; Weston-Dawkes et al., 2021); such coupled interactions are not considered below.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…Under a limited range of operating conditions – namely, for surfaces with millimetric characteristic dimensions or oscillation frequencies as low as several hundred hertz – this steady force has been observed to transition from strong repulsion to weak suction of less than 1 gf (Andrade, Ramos, Adamowski, & Marzo, 2020; Sadayuki, 2002; Takasaki, Terada, Kato, Ishino, & Mizuno, 2010; Yoshimoto, Shou, & Somaya, 2013). Recent experiments have shown that this minor attractive load capacity is magnified a thousand fold when the stiffness of the oscillator is reduced substantially to provide pronounced flexural deformations that may be subject to non-negligible fluid–structure coupling (Colasante, 2015; Weston-Dawkes et al., 2021). A preliminary theoretical analysis (Ramanarayanan & Sánchez, 2022) indicated that the range of operating conditions under which attraction occurs, as well as the magnitude of the resulting force, grows substantially with the wavenumber of oscillation, i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, dual-wheel modules were created to balance forces on surfaces with varying curvatures and increase friction [ 24 ]. The spring plate connection between the wheels can isolate the additional force generated by the tyre mass when the suction module vibrates [ 91 ]. Adding two DOFs to magnetic adhesion wheels can achieve shape-adaptive capabilities while guaranteeing that the adhesion force is always directed normally to the surface [ 22 ].…”
Section: Locomotion Mechanisms For Climbing Robotsmentioning
confidence: 99%
“…Suction is useful for holding objects [6] [12] [13] because it acts as a function of adsorption, increasing surface friction. Blowing creates a thin layer of air between the FDR device and the contact target and reduces surface friction [14]. The advantage 1 IEEE ROBOTICS AND AUTOMATION LETTERS.…”
Section: Introductionmentioning
confidence: 99%